2007
DOI: 10.1002/maco.200704070
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion resistance of three austenitic stainless steels for biomedical applications

Abstract: The resistance to localized corrosion of three austenitic stainless steels (SS), specifically the ASTM F-138 which is widely used in several biomedical applications, the DIN 1.4460 high N, and the DIN 1.4970 was investigated in this study by electrochemical techniques including potentiodynamic polarization and electrochemical impedance spectroscopy measurements in a phosphatebuffered solution. The DIN 1.4460 high N and the DIN 1.4970 were tested in this study for the reason they do not form any ferromagnetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
0
12
0
2
Order By: Relevance
“…In this way, the coated implants will not only have the good mechanical properties of the substrate but also an enhanced osseointegration and bioactivity due to the calcium phosphate layer [96]. Terada et al [97] have evaluated the significant effects of 316L SS on the clinical success and Fathi et al [98] studied the bone tissue response and histopathological results of HAP coated/ uncoated metallic implants (316L SS and Ti) in animals. The results showed that different substrates had pronounced effects on the histopathological response to HAP coated on different implants with beneficial corrosion resistance of the coatings.…”
Section: Corrosion In Dentistrymentioning
confidence: 99%
“…In this way, the coated implants will not only have the good mechanical properties of the substrate but also an enhanced osseointegration and bioactivity due to the calcium phosphate layer [96]. Terada et al [97] have evaluated the significant effects of 316L SS on the clinical success and Fathi et al [98] studied the bone tissue response and histopathological results of HAP coated/ uncoated metallic implants (316L SS and Ti) in animals. The results showed that different substrates had pronounced effects on the histopathological response to HAP coated on different implants with beneficial corrosion resistance of the coatings.…”
Section: Corrosion In Dentistrymentioning
confidence: 99%
“…Ti and Ti alloys are by far the most used materials for body implants; however, their excessive prices make them unaffordable to the health public system of underdeveloped countries. Thus researches on biocompatibility and corrosion resistance on simulating body fluid solutions of less expensive materials are under way in many countries [1,2]. Milosev and Strehblow [3] studied the corrosion behavior of stainless steels in a physiological solution and concluded that the properties of the passive layer, account for the corrosion resistance of orthopedic implants produced with these materials.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, the articulated implants that are exposed to high loads and severe wear due to the patient's movement can be mentioned. Moreover, the degradation of metallic implants inside the human body may not only impair the integrity of the material, but also generate biocompatibility problems such as infection or allergic reactions, leading to premature removal of the implant (Rondelli et al 1997, Terada et al 2007. The derived detritus is harmful to the tissues that are in contact with the implant and can be taken into the bloodstream, settling in organs and impairing their functions.…”
Section: Introductionmentioning
confidence: 98%